Established and suggested exposures on CLL/SLL etiology: Results from the CLL-MCC-Spain study. (February 2018) - Benavente, Yolanda; Casabonne, Delphine; Costas, Laura; Robles, Claudia; Alonso, Esther; de la Banda, Esmeralda; Gonzalez-Barca, Eva; Marcos-Gragera, Rafael; Llorca, Javier; Tardón, Adonina; Monleon, José J.; Aymerich, Marta; et al.
Highlights: Knowledge is limited in relation to chornic lymphocytic leukemia etiology (CLL). Enviromental exposures and CLL are assessed through a case control study in Spain. CLL are more likely to have first degree relatives with hematological cancer. Working in agriculture is more frequent in CLL cases. Abstract: Introduction: Chronic Lymphocytic Leukemia (CLL/SLL) is the most common adult leukemia in Western countries. Although it is mostly an indolent disease it is still incurable and with limited knowledge in relation to its etiology. We aim to confirm and quantify established risk factors for CLL/SLL using a multi-center epidemiological population-based case-control study on CLL/SLL as well as to explore new exposures inconclusively associated with CLL/SLL Methods: Using the framework provided by the large MCC-Spain case-control study, we explored established and suggested risk factors associated with CLL/SLL using data collected through a face-to-face interview. We estimated odds ratios (OR) and confidence intervals (CI) adjusted by basic confounders, in 1, 845 controls from the general population and 560 CLL/SLL from 5 different Spanish regions. Results: Among the established risk factors, CLL/SLL cases were 3 times more likely to report first degree relatives with an hematological cancer (OR = 3.11, 95% CI 2.10 to 4.61) and nearly twice likely to have ever worked in agriculture (OR = 1.70, 95% CI = 1.34 to 2.16). New findings suggest that women with CLL/SLL were more likely to have central obesity (OR = 1.67 95% CI = 1.12 to 2.48). An inverse association was found for current alcohol consumption ( p -trend<0.016) and for type II diabetes. Conclusion: We confirmed previous established risk factors for CLL/SLL. Among the new findings, further research of central obesity as preventable exposure and the treatment for type II diabetes are warranted.